2007
DOI: 10.1080/00016340701625446
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor sex steroid hormone receptors, distribution and expression in pre‐ and postmenopausal stress urinary incontinent women

Abstract: The para-urethral ECM is a target for sex steroid hormones mediated by the respective receptor. The significant higher expression of ER-beta protein in the pre-menopausal SUI-group was not reflected by a corresponding up-regulation of mRNA which was poorly expressed in all groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
(34 reference statements)
0
27
0
2
Order By: Relevance
“…periurethral tissue) or on the musculus levator ani [6][7][8][9]. Only little is known about reaction of the posterior vaginal wall influenced by steroid receptor expression.…”
Section: Introductionmentioning
confidence: 99%
“…periurethral tissue) or on the musculus levator ani [6][7][8][9]. Only little is known about reaction of the posterior vaginal wall influenced by steroid receptor expression.…”
Section: Introductionmentioning
confidence: 99%
“…The lower urinary tract, due to its common embryological origin with the female reproductive system, is sensitive to steroid hormones. Oestrogen, androgen and progesterone receptors have been recognised throughout the length of the urinary tract and in particular in structures directly relevant to urinary incontinence, such as the urethra, the vagina and the pelvic floor musculature including its ligaments, fascia and connective tissues . Estrogens increase vascularity, the sensitivity of a‐adrenergic receptors of smooth muscles, as well as the number of superficial and intermediate cells of the bladder and urethra, affecting also the nervous control of micturition.…”
Section: Introductionmentioning
confidence: 99%
“…Even though estrogen receptor concentrations are higher in the urethra than the bladder trigone,(16) the paraurethral tissues and bladder outlet are both targets for gonadal steroid hormones. (17) It is therefore suggested that the observed protective effects of oral contraceptives on urinary incontinence in the present study, reflects an influence of estrogen on urethral function and morphology. (18) This assumption is corroborated by experimental studies where estrogen increases urethral sphincter muscle contractility and urethral closing pressure.…”
Section: Discussionmentioning
confidence: 52%